(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
The aims of the present research are two folds: to know the phenotypic diversity and to reconstruct the cross-breeding pattern of local cattle in Banyuwangi. Based on three sampling areas, it was found that there were 32 phenotypic cattle (10 in the sub districts of Rogojampi, 16 in Tegaldlimo and 6 in Glagah areas). The phenotypic varieties were caused by two factors, namely the flow of genetic intervention of the other local cattle (Bali, Ongole, and Brahman cattle) and the artificial insemination program using the semen of Limousine, Simmental, Aberdeen Angus and Santa Gertrudis cattle. Â© 2010 Biodiversitas, Journal of Biological Diversity Key words: flow of genetic intervention, local cattle, phenotypic variation